PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP PEMAHAMAN KONSEP PETA DI SEKOLAH DASAR - Pina; Budi Febriyanto; Ani Rosidah (STKIP Subang, 2025)
This study aims to analyze the effect of interactive learning media on elementary school students’ understanding of map concepts. The method used was a quasi-experimental design with a nonequivalent control group. Data were collected through pre-test and post-test, then analyzed using normality test, homogeneity test, independent sample t-test, and N-Gain calculation. The results of the normality test showed that the pre-test in the experimental class had a significance value of 0.079 and the control class 0.154, while in the post-test the experimental class was 0.052 and the control class 0.128. All values were greater than 0.05, indicating that the data were normally distributed. The homogeneity test also showed homogeneous data with a significance value of 0.592 for the pre-test and 0.728 for the post-test. The average post-test score in the experimental class was 90.12, higher than the control class with 81.48. The N-Gain average of the experimental class was 81.19 categorized as high and very effective, while the control class reached 68.83 categorized as moderate and fairly effective. The independent sample t-test produced a significance value of 0.000, indicating a significant difference between the two groups. Thus, interactive learning media is more effective than conventional learning in improving students’ understanding of map concepts.